RURAL SPACE. LAND USE AND LAND STRUCTURE. CASE STUDY: CLUJ COUNTY, ROMANIA - ADINA-MARIA PUŞCAŞU (Studia Universitatis Babeş-Bolyai: Geographia, 2014)
Rural Space. Land Use and Land Structure. Case Study: Cluj County, Romania. The purpose of this paper is to assess the rural area of Cluj County, by highlighting certain aspects conclusive in demonstrating the rurality of this territory. Consequently, the rural area is being described in terms of number of inhabitants, population density, the degree of comfort and equipment of households by the existence or the access to various services and in terms of land use, resulting values which reflect the current situation of rurality in Cluj. To explain rurality of a territory involves the appeal to different fields of geographical investigations correlated with a wide range of topics (sociology, politics, anthropology, ecology, history).